Attentional Orienting and Dorsal Visual Stream Decline: Review of Behavioral and EEG Studies - Sciberras-Lim, Evatte T.; Lambert, Anthony J. (Frontiers in Aging Neuroscience, 2017)
Every day we are faced with an overwhelming influx of visual information. Visual attention acts as the filtering mechanism that enables us to focus our limited neural resources, by selectively processing only the most relevant and/or salient aspects of our visual environment. The ability to shift attention to the most behaviorally relevant items enables us to successfully navigate and interact with our surroundings. The dorsal visual stream is important for the rapid and efficient visuospatial orienting of attention. Unfortunately, recent evidence suggests that the dorsal visual stream may be especially vulnerable to age-related decline, with significant deterioration becoming evident quite early in the ageing process. Yet, despite the significant age-related declines to the dorsal visual stream, the visuospatial orienting of attention appears relatively well preserved in older adults, at least in the early stages of ageing. The maintenance of visuospatial orienting of attention in older adults appears to be facilitated by the engagement of compensatory neural mechanisms. In particular, older adults demonstrate heightened activity in the frontal regions to compensate for the reduced activity in the posterior sensory regions. These findings suggest that older adults are more reliant on control processes mediated by the anterior regions of the frontoparietal attention network to compensate for less efficient sensory processing within the posterior sensory cortices.